2020
DOI: 10.21203/rs.2.22360/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spirulina platensis enhances immune status, inflammatory and oxidative markers of HIV patients on antiretroviral therapy in Cameroon

Abstract: Background Spirulina platensis is traditionally used as a food supplement with a potential strengthening of the immune system, inhibition of the replication of some viruses, and lipid-lowering effect. The aim of this study was to determine its effect on the inflammatory, immunological, and oxidative status of HIV patients on antiretroviral therapy (ART). Methods We performed a study on 62 HIV patients on ART (Tenofovir-Lamivudine-Efavirenz) divided into 2 groups. Group I, supplemented with 10 grams of Spirulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, there is limited information on the investigation of SP confirming the mechanism of antioxidant and anti-inflammatory effects and the impact on the quality of life in the HIV-positive population taking HAART. Thus far, it has been shown that supplementation with Spirulina platensis could improve the immune status of HIV patients on ART and decrease inflammatory and pro-oxidant levels [ 190 ]. The development of more clinical studies to confirm the SP protective effect in this population will answer many questions.…”
Section: Combined and Synergistic Therapeutic Actions Of Haart And Spmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited information on the investigation of SP confirming the mechanism of antioxidant and anti-inflammatory effects and the impact on the quality of life in the HIV-positive population taking HAART. Thus far, it has been shown that supplementation with Spirulina platensis could improve the immune status of HIV patients on ART and decrease inflammatory and pro-oxidant levels [ 190 ]. The development of more clinical studies to confirm the SP protective effect in this population will answer many questions.…”
Section: Combined and Synergistic Therapeutic Actions Of Haart And Spmentioning
confidence: 99%
“…The development of more clinical studies to confirm the SP protective effect in this population will answer many questions. The recommended concentrations of SP for daily supplementation varies, as studies have successfully used 19 g [ 185 ], 5 g [ 186 ], and 10 g [ 190 , 191 ].…”
Section: Combined and Synergistic Therapeutic Actions Of Haart And Spmentioning
confidence: 99%
“…The use of spirulina nutritional supplements in patients with HIV receiving antiretroviral therapy (62 people) reduced the viral load and reduced the levels of TNF-α and prooxidant markers. Moor et al [153] suggest daily use of spirulina in treating patients with HIV infection, which can improve the state of the immune status and reduce the level of inflammation and prooxidants. and, more importantly, TNF-α.…”
Section: Effects Of Microalgae and Cyanobacteria Polysaccharides On T...mentioning
confidence: 99%
“…S. platensis is commercially produced because of its high digestibility and interesting protein content (46-71%) of the dry weight of the algae, as well as high amounts of essential fatty acids and amino acids, vitamins, pigments (phycobiliproteins and carotenoids) and polysaccharides (Zhu et al, 2018;Corrêa and Teixeira, 2021). This cyanobacterium has gained in importance and international demand not only for its nutritional and therapeutic properties but also for its applications in human and animal nutrition, therapeutics and diagnostics (Panjiar et al, 2017;Ama Moor et al, 2020). It is generally recognized as safe from the US Food and Drug Administration and considered as the most complete food for the future by the Food and Agriculture Organization of the United Nations (Goulamabasse, 2018;Branyikova and Lucakova, 2020).…”
Section: Introductionmentioning
confidence: 99%